PMM.27 Unresolved proteinuria after pre-eclampsia: detecting renal disease. (9th June 2014) - Roberts, AL; Loughna, P; Ferraro, A; Broughton-Pipkin, F
Abstract : Abnormal proteinuria (a urinary protein creatinine ratio (PCR) >30 mg/mmol), combined with new onset hypertension in pregnancy, is the hallmark of pre-eclampsia. NICE guidelines 1 recommend that a urine dipstick test is performed at the 6–8 week postnatal check to ensure resolution but there is evidence to suggest that follow up is often inadequate. Via a designated postnatal clinic we studied 315 women whose pregnancy had been complicated by pre-eclampsia. None had proteinuria at booking or a history of chronic kidney disease (CKD) but 29 women (9.2%) had a PCR >30 mg/mmol (mean 8 weeks postpartum). Subsequent follow-up was in primary care, though renal referral was recommended if proteinuria persisted. Amongst the 29, proteinuria persisted at 6 months postpartum in nine women (31%). Two were subsequently diagnosed with CKD. One declined investigation despite heavy proteinuria and hypertension and is now pregnant again. Another two still have low level proteinuria. Three women were lost to follow up. One was referred to another hospital. In most women proteinuria will resolve by 6 months postpartum, however in a few it is persistent and it occasionally represents undiagnosed renal disease. Postnatal follow up is essential to ensure these women do not remain undiagnosed. Reference: NICE. Hypertension in Pregnancy: the management of hypertensive disorders in pregnancy. 2010